Exclusive skeletal muscle correction does not modulate dystrophic heart disease in the aged mdx model of Duchenne cardiomyopathy - Wasala, Nalinda B. (Oxford University Press, 2013)
Duchenne muscular dystrophy (DMD) is characterized by severe degeneration and necrosis of both skeletal and cardiac muscle. While many experimental therapies have shown great promise in treating skeletal muscle disease, an effective therapy for Duchenne cardiomyopathy remains a challenge in large animal models and human patients. The current views on cardiac consequences of skeletal muscle-centered therapy are controversial. Studies performed in young adult mdx mice (a mild DMD mouse model) have yielded opposing results. Since mdx mice do not develop dystrophic cardiomyopathy until ≥21 months of age, we reasoned that old mdx mice may represent a better model to assess the impact of skeletal muscle rescue on dystrophic heart disease. Here, we aged skeletal muscle-specific micro-dystrophin transgenic mdx mice to 23 months and examined the cardiac phenotype. As expected, transgenic mdx mice had minimal skeletal muscle disease and they also outperformed original mdx mice on treadmill running. On cardiac examination, the dystrophin-null heart of transgenic mdx mice displayed severe cardiomyopathy matching that of non-transgenic mdx mice. Specifically, both the strains showed similar heart fibrosis and cardiac function deterioration in systole and diastole. Cardiac output and ejection fraction were also equally compromised. Our results suggest that skeletal muscle rescue neither aggravates nor alleviates cardiomyopathy in aged mdx mice. These findings underscore the importance of treating both skeletal and cardiac muscles in DMD therapy.